PENANGANAN KELUHAN PELANGGAN COFFEE SHOP OLEH BARISTA DI LETON COFFEE PEKANBARU - Zahara, Ghina; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Currently, the café business in the city of Pekanbaru is increasingly enjoyed by all layers of society, one of which is Leton Coffee. Behind the establishment of a café, excellent service is necessary to attract customers, with one form of excellent service being handling Customer complaints. This study aims to determine the factors that cause customers to complain to baristas, the efforts of baristas in handling Customer complaints, and the management efforts at Leton Coffee Pekanbaru in preparing professional baristas to deal with complaints. This research is a descriptive qualitative study with data collection through interviews, observations, and documentation. The results obtained indicate that the main factor behind complaints at Leton Coffee Pekanbaru is dissatisfaction and discomfort felt by customers. The efforts of cashiers and baristas in handling complaints involve using the HEAT method, and the Coffee shop management's efforts in complaint handling include conducting Training for Leton Coffee Pekanbaru employees every month. Keywords: Coffee Shop, HEAT, Excellent Service, Leton Coffee, Handling Complaints